DEVELOPMENT OF VOLLEYBALL LOWER PASSING SKILL MODEL FOR JUNIOR HIGH SCHOOL EXTRACURRICULARS - Pangesti, Khansa Dwi (Gladi : Jurnal Ilmu Keolahragaan, 2024)
Abstract This study aims to obtain empirical data on the effectiveness and results of the volleyball lower passing skills model. This type of research is research and development (R&D) with a pre-test and post-test design. The data analysis technique collects effectiveness test data using the t test with SPSS software. The effectiveness test was conducted on volleyball extracurricular participants at SMPN 15 Depok City, totaling 40 children who were given treatment using a variety of volleyball lower passing skill models for 4 meetings. The volleyball lower passing research instrument was carried out with a 1-minute lower passing test. The results of the study based on expert validation, it can be said that there are 12 models of lower passing skills based on media modifications that are considered feasible. And based on the quality of the model, this model is in the GOOD category, with a score of 88. In addition, after testing the effectiveness of the model, it can be seen that this skill model is effective for improving volleyball lower passing skills with a p value = 0.000 <0.005. so it can be interpreted that there is a significant difference between the average of the experimental group and the control group. So it can be concluded that giving experimental treatment has a significant effect compared to the control group.